THE EFFECT OF WORDWALL BASED EDUGAMES MEDIA ON STUDENTS LEARNING MOTIVATION IN MATHEMATICS LEARNING - Annisa, Rivanda Nur; Nur, Iyan Rosita Dewi (Universitas Muhammadiyah Metro, 2025)
Low student motivation in learning mathematics is a common challenge in mathematics learning. The use of Wordwall-based edugames media is an alternative solution to increase student motivation. This study aims to analyze the effect of using Wordwall-based edugames media on student learning motivation in mathematics learning for grade VII. This study uses a quantitative approach with a pre-experimental method. The design used in this study is a one-shot case study. This design is used to observe the effects of treatment directly after learning without a pre-test. The population in this study were all grade VII students at SMPN 3 Cikarang Selatan. The sample in this study was class VII.5 totaling 38 students who were taken using a purposive sampling technique. The instruments used in this study were a questionnaire on the use of Wordwall-based edugames media and a questionnaire on student learning motivation. Data were collected through a student learning motivation questionnaire given after learning using Wordwall-based edugames media and analyzed using a simple linear regression test with the help of SPSS Statistics software version 25. The results showed that there was a positive effect of Wordwall-based edugames media on student learning motivation in mathematics learning by 31.8%. Rendahnya motivasi siswa dalam mempelajari matematika menjadi suatu tantangan yang sering terjadi dalam pembelajaran matematika. Penggunaan media edugames berbasis Wordwall menjadi alternatif solusi untuk meningkatkan motivasi siswa. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media edugames berbasis Wordwall terhadap motivasi belajar siswa dalam pembelajaran matematika kelas VII. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre-eksperimen. Desain yang digunakan dalam penelitian ini adalah one-shot case study. Desain ini digunakan untuk mengamati efek perlakuan secara langsung setelah pembelajaran tanpa dilakukan pre-test. Populasi pada penelitian ini adalah seluruh siswa kelas VII di SMPN 3 Cikarang Selatan. Sampel pada penelitian ini adalah 38 siswa kelas VII.5 yang diambil menggunakan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini, yaitu angket penggunaan media edugames berbasis Wordwall dan angket motivasi belajar siswa. Data dikumpulkan melalui angket motivasi belajar siswa yang diberikan setelah pembelajaran menggunakan media edugames berbasis Wordwall dan dianalisis menggunakan uji regresi linear sederhana dengan bantuan Software SPSS Statistics versi 25. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dari media edugames berbasis Wordwall terhadap motivasi belajar siswa dalam pembelajaran matematika sebesar 31,8%